Massive losses and gains of northern land carbon stocks since the Last Glacial Maximum - Lindgren, Amelie; Kuhry, Peter; Holloway, Max; Lu, Zhengyao ; 0000-0002-5911-7110; Tanski, George; Hugelius, Gustaf (Science Advances, 2025)
The dynamics of atmospheric CO2 concentrations during and following the last deglaciation have mainly been ascribed to carbon release from and uptake in oceans, primarily in the Southern Ocean. But recent studies also point toward a terrestrial influence. We quantify dynamic changes to northern terrestrial carbon stocks from the Last Glacial Maximum (21,000 years) until present at millennial time steps using a combination of paleo-data and climate-biome modeling. During the deglaciation, northern land carbon storage declined by >300 petagrams of carbon with a minimum around 11,000 years, followed by progressively higher land carbon stocks during the Holocene. We find evidence that dynamic changes in terrestrial land carbon stocks were of a scale to exert large influence on atmospheric CO2 concentrations and that postglacial terrestrial carbon stock dynamics were dominated by losses from permafrost-affected loess and gains into peatlands.